PENGARUH LOKASI DAN HARGA TERHADAP LOYALITAS MELALUI KEPUTUSAN PEMBELIAN PADA LAVAS’CO COFFEE AND RESTO DI KOTA TIMIKA - RESTY MADIA BATO'SAU'; Abu Bakar (Jurnal Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of location and price on loyalty through purchasing decisions at Lavas'co Coffee and Resto in Timika City. The data collected in this study are qualitative data and quantitative data sourced from Lavas'co Coffee and Resto in Timika City. The number of samples in this study was 100. Data collection techniques in this study were observation and questionnaires and used SEM-PLS (Structure Equation Model Partial Least Square) analysis and the application used SmartPLS Version 4.0. The results of the analysis show that location and price have a positive and significant effect on purchasing decisions at Lavas'co Coffee and Resto. Location does not have a positive and significant effect on consumer loyalty at Lavas'co Coffee and Resto, while price has a positive and significant effect on consumer loyalty at Lavas'co Coffee and Resto. Purchasing decisions have a positive and significant effect on consumer loyalty at Lavas'co Coffee and Resto. Location and price have a significant effect on consumer loyalty through purchasing decisions at Lavas'co Coffee and Resto.